Emerging frontiers in cHCC-CCA organoid models: bridging stem cell innovation to precision oncology - Juntao Sun; Wenqing Liu; Ye Gao; Yuehuan Liu (Egyptian Liver Journal)
Abstract Combined hepatocellular-cholangiocarcinoma (cHCC-CCA) is a rare and complex liver malignancy characterized by diverse clinical features and unfavorable therapeutic responses. The utilization of organoid technology, a nascent research methodology, demonstrates considerable promise in replicating the pathophysiological aspects of cHCC-CCA, facilitating disease modeling and enhancing drug screening efficacy. This review provides a comprehensive overview of the progression in establishing cHCC-CCA organoid models derived from both adult stem cells and induced pluripotent stem cells (iPSCs) within the scientific community. Organoids constructed from Lgr5 + cells and various adult stem cell populations exhibit robust expansion capability and the capacity for hepatic parenchymal cell differentiation. The advent of iPSC-generated liver buds and cholangiocyte-like organoids has broadened the horizons of this field. Additionally, leveraging organoids in disease modeling, drug screening, and personalized therapy offers new hope for precision medicine. Despite inherent constraints, the advancement of organoid technology is poised to catalyze substantial advancements in the investigation and treatment of cHCC-CCA. The aim of this work is to provide a detailed analysis of the current state of organoid technology in the context of cHCC-CCA research and to highlight the potential future directions for this promising field.